A note on humpback whales (Megaptera novaeangliae) in the central Indian Ocean - Anderson, R. Charles; Isha,; Sutaria , Dipani; de Vos , Asha (J. Cetacean Res. Manage., 2022)
In the central Indian Ocean, humpback whales (Megaptera novaeangliae) are rare. Records from southern India, Sri Lanka, Maldives and the Chagos Archipelago (n = 68) were compiled and show a bimodal pattern of seasonal occurrence. Those occurring during the northern winter (December to March) are known from other studies to belong to the Arabian Sea humpback whale population. There have been no humpback whales recorded in Maldives during the northern winter since 2002, suggesting a possible range contraction for the Arabian Sea humpback whale population. Humpback whales occurring during the southern winter (June to October) are assumed to belong to the southwest Indian Ocean population (IWC breeding stock C). In this case, numbers of opportunistic sightings are increasing and the population appears to be spreading northwards as it recovers from commercial whaling, with several recent southern winter records from as far north as 5°N in northern Maldives and southern Sri Lanka. For this southern hemisphere population, calves are first seen in August, with numbers of calves increasing in September and October. For both populations, interactions with regional fisheries, particularly pelagic gillnetting, may be a major cause of mortality.